Selective radical cyclisation of propargyl bromoethers to tetrahydrofuran derivatives via electrogenerated nickel(I) tetramethylcyclam - Esteves, Ana Paula (2007)
The controlled-potential reduction of [1-bromo-2-methoxy-2-(prop-2'-ynyloxy)ethyl]benzene(1a), 1-[2-bromo-2-phenyl-1-(prop-2'-ynyloxy)ethyl]-4-methoxybenzene (1b) and 2-bromo-3-(3',4'-dimethoxyphenyl)-propargyloxypropanamide (1c) catalysed by (1,4,8,11-tetramethyl-1,4,8,11 tetraazacyclotetradecane)nickel(I), [Ni(tmc)]+, at a vitreous carbon cathode in DMF/Et4NBF4 leads to 2-methoxy-4-methylene-3-phenyl-tetrahydrofuran (2a), 2-(4'-methoxyphenyl)-4-methylene-3-phenyl-tetrahydrofuran (2b) and 2-(3',4'-dimethoxyphenyl)-3-carbamoyl-4-methylenetetrahydrofuran (2c), respectively, in very high yields.